The effects of HNO3 and CH3COOH on the aqueous phase hydroxylation of benzene to phenol by hydrogen peroxide over TS-1 catalyst - Chankeaw, Yaowaluk; Manosak, Rudemas; Mongkhonsi, Tharathon (Engineering and Applied Science Research, 2015)
The direct synthesis of phenol by benzene hydroxylation with hydrogen peroxide over titanium silicalite-1 (TS-1) catalyst is carried out in a three phase stainless steel reactor system. The effects of HNO3 and CH3COOH on the concentration are studied. It was found that the adding of HNO3 and CH3COOH could enhance the conversion of benzene to phenol. The concentration that of HNO3 also affects extend of the reaction.